Kobiety Wielkiej Armii Napoleona. Szkic do portretu - Kaniewski, Piotr; Kostrzewa, Krzysztof (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
Sutlers were women acompanied Napoleon’s army in the wars conducted by Kaiser. This covers: laundress, cantiniére, hawkers, prostitutes. Moreover some of them also women, which distinguished themselves in fight on the battlefileld. Each sutlers was assigned to a specific regiment. The evolution of the phenomenon occurring during the French Revolution. At that time, at the time of dissolution of the army Bourbon and the formation of battalions of volunteers, their number in the ranks of the French a significant increase. Along with her husband, brother, father, sometimes also with a lover, they leave their provincial town, going to the front line. Then she tried, as long as possible to be under the banner of the Republic, demonstrating its usefulness for the defenders of the homeland. Then it completely took over the trade, liquor, supplied various small objects such as combs, mirrors. It is worth noting that in a bad provisioning the army – in which there was often hungry – not soldiers by providing food was not to be underestimated. It is sutlers, pulling his troops in cars supplied with food, as well as the alcohol is required for all medical procedures. Both the revolutionary authorities, as well as afterwards by Napoleon himself tried to limit the number of women in the military. For this purpose, are introduced various regulatory constraints, such as they had to prove ownership of their profession. Position of women in the French army has changed only with the battle of Austerlitz, in which distinguished themselves in active combat on the battlefield, and since 1807, the Poles found themselves in the ranks of Napoleon gave evidence of his extraordinary courage. Among them, the most famous Polish sutlers were: Helena Kurdwanówna and Joanna śubrowa. The major wars of Napoleon, in which the Poles played a big role in the campaign include Spanish, war in 1809 and 1812.